Powering the Immune System: Mitochondria in Immune Function and Deficiency - Melissa A. Walker; Stefano Volpi; Katherine B. Sims; Jolan E. Walter; Elisabetta Traggiai (Journal of Immunology Research)
Mitochondria are critical subcellular organelles that are required for several metabolic processes, including oxidative phosphorylation, as well as signaling and tissue-specific processes. Current understanding of the role of mitochondria in both the innate and adaptive immune systems is expanding. Concurrently, immunodeficiencies arising from perturbation of mitochondrial elements are increasingly recognized. Recent observations of immune dysfunction and increased incidence of infection in patients with primary mitochondrial disorders further support an important role for mitochondria in the proper function of the immune system. Here we review current findings.